P53 gene: major mutations in neoplasias and anticancer gene therapy Gene p53: principais mutações em neoplasias e terapia gênica anticâncer - Caroline Rocha de Oliveira Lima (Ciência Rural, 2012)
The p53 gene encodes a protein that has molecular weight of 53kD and is also called p53 protein, being constantly studied for its classic concept of "genome guardian". This gene plays a range of essential functions to ensure the cell cycle control, in addition to playing a central role in carcinogenesis. With respect to neoplasias, it prevents the neoplastic transformation through three intricate mechanisms. Depending on the extent of the mutation, different responses may be sent by p53 and those range since the disruption of the cell cycle, the correction of the mutation through the activation of repair proteins or still, the induction of senescence or cell death by apoptosis. This review aims to address the structural and functional aspects of the p53 gene and protein, and also reaffirm their participation in the carcinogenesis control, approaching their major mutations and the anticancer gene therapy involving this gene. O gene p53 codifica uma proteína que tem peso molecular de 53kD e é também chamada de proteína p53, sendo constantemente estudado por seu conceito clássico de "guardião do genoma". Esse gene desempenha uma série de funções essenciais para garantir o controle do ciclo celular, além de desempenhar um papel central na carcinogênese. Com relação a neoplasias, impede a transformação neoplásica através de três mecanismos intrincados. Dependendo da extensão da mutação, diferentes respostas podem ser enviadas por p53 desde a ruptura do ciclo celular, a correção da mutação através da ativação de proteínas de reparo ou, ainda, a indução de senescência ou morte celular por apoptose. Esta revisão visa a abordar os aspectos estruturais e funcionais do gene p53 e proteína, e também reafirmar a sua participação no controle da carcinogênese, abordando suas principais mutações e a contribuição para a terapia gênica anticâncer.